Tyutchev in the poetic world of Alexander Kushner - Поборчая, Ирина Петровна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The subject of the research in the article is peculiarities of dialogism in Kushner's poetry.The main focus here is intertextual connection between Kushner's works and F.I. Tyutchev's lyrics, motive and image parallels which describe modern poet's specific way of understanding classical literature of XIX century. It is shown that Tyutchev's discourse determines many ways of Kushner's poetic ideas where reminiscences and allusions become a special tool to create his own world picture, reflected in poet's lyrics.